The cobra [compact disc, unabridged] - Forsyth, Frederick, 1938- (Penguin Audio, 2010)
For decades, the world has been fighting the drug cartels, and losing, their billions of dollars making them the most powerful and destructive organizations on earth. Until one man is asked to take charge. Paul Devereaux used to run Special Operations for the CIA before they retired him for being too ruthless. Now he can have anything he requires, do anything he thinks necessary. The war is on.